Creating a Digital Thematic Map Based on Spatial Data in Alahair Village Using the QGIS 3.22.4 Application - Arisman Adnan; Sul Kantri Rahma Wanti; Windy Lasma Sari Purba; Rahwana Saputra; Fikri Marwansyah; Defrinaldi Absari; Kesi Marseliani; Nabilah Fitriyyah Delfira; Sillaturahim; Sukma Novia Syafitri; Wirda Hia (PT FORMOSA CENDEKIA GLOBAL, 2023)
Located in the Meranti Islands Regency of Riau Province, Alahair Village is a part of the Tebing Tinggi subdistrict. Alahair Village faces a number of data-related issues, such as data that isn't validated according to the field, unstructured data, and the need to find data quickly; requests from agencies at the sub-district, district, and provincial levels for data from the village; and the fact that when staff changes occur in the village, the data stored in the soft file is lost. Soil types, political boundaries, roads, irrigation zones, altitude, weather, and population can all be stored and managed with the help of spatial and non-spatial data. QGIS 3.22.4 is one such GIS-based program, and it can be used to make maps. Service to the community is accomplished through the following procedures: obtaining a statement of willingness to collaborate and partner; identifying village data needs; collecting village data; processing village data; creating thematic maps; discussing the results of thematic maps; holding workshops to discuss thematic map findings. Lecturers, students, and partners involved in mentoring in the field carry out this community service activity, producing a thematic map with generational, occupational, and educational classifications. Making a thematic map is the presentation of village data in the form of a map which contains village data which will later be easily accessed as a basis for information for the spatial needs of the village's sustainable development plan.